Edible urban commons for resilient neighbourhoods in light of the pandemic. (February 2021) - Sardeshpande, Mallika; Rupprecht, Christoph; Russo, Alessio
Abstract: Edible urban commons can aid recovery from the pandemic-induced crises, and build urban resilience to future disruptions.